Reversible sensory neuropathy in mitochondrial trifunctional protein deficiency - Sarah Catharina Grünert; Matthias Eckenweiler; Ute Spiekerkoetter (JIMD Reports, 2022)
Abstract Axonal peripheral neuropathy is a common complication of mitochondrial trifunctional protein (MTP) deficiency and long‐chain 3‐hydroxyacyl‐CoA dehydrogenase deficiency that is usually considered progressive. Current treatment strategies are not able to fully prevent neuropathic symptoms in the majority of patients. We herein report three sisters with genetically proven MTP deficiency who were untreated until adolescence, when electrophysiological studies first revealed isolated axonal sensory neuropathy. Apart from mild exercise intolerance and missing deep tendon reflexes of the lower extremities, all three girls were clinically asymptomatic. A fat‐reduced and fat‐modified diet together with a reduction of the nocturnal fasting time resulted in complete normalisation of the electrophysiological studies after 1 year of dietary treatment. Our findings suggest that neuropathy might be responsive to dietary interventions in MTP patients at a very early stage of disease.